2020
DOI: 10.1364/ol.386039
|View full text |Cite
|
Sign up to set email alerts
|

Diamond Raman oscillator operating at 1178  nm

Abstract: In this contribution, we report high-power Raman frequency downconversion based on an Yb-doped fiber amplifier and a linear external diamond Raman cavity. A maximum output power of 136 W with nearly diffraction-limited beam quality was achieved by pumping in quasi-continuous-wave mode with 10% duty cycle and 10 ms on-time duration. For continuous-wave operation, we achieved record average power of 46 W centered at 1178 nm. The emergence of stimulated Brillouin scattering in diamond is further investigated. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…However, a secondary peak at a separation 73.4 GHz appears on the longer wavelength side of the Stokes line with intensity 15.7 dB lower. The frequency shift matched the Brillouin frequency previously reported in the references of [25,32,40]. The emergence of SBS adversely affects the output stability and further power scaling due to the strong nonlinear coupling from the SRS field.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…However, a secondary peak at a separation 73.4 GHz appears on the longer wavelength side of the Stokes line with intensity 15.7 dB lower. The frequency shift matched the Brillouin frequency previously reported in the references of [25,32,40]. The emergence of SBS adversely affects the output stability and further power scaling due to the strong nonlinear coupling from the SRS field.…”
Section: Resultssupporting
confidence: 81%
“…Diamond has outstanding advantages in the high-power regime [26,29,30] by virtue of its extremely outstanding thermophysical and SRS properties [31], high thermal conductivity (2200 W m −1 K −1 ), low linear thermal expansion coefficient (1.1 × 10 −6 K −1 ), wide optical transmission spectrum from 225 nm to mid IR, high Raman gain coefficient from 8 to 10 cm GW −1 at 1064 nm, large Raman frequency shift of 1332.3 cm −1 . Recently, several reports have shown that Raman lasing in diamond is an interesting method for developing 1178 nm laser based on mature Yb-doped fiber (YDF) lasers at 1018 nm as pumps [32][33][34]. In [32], a diamond Raman laser (DRL) converted a continuous pumping power of 250 W at 1018 nm to the first-order Stokes wave at 1178 nm with the output power of 46 W having a conversion efficiency of 23% and a slope efficiency of 25%.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A multiorder Stokes laser can be achieved by SRS process when the pumping laser intensity is high enough [18,19]. Previously, numerous solid-state Raman mediums have been developed, including CVD diamond [20][21][22], YVO 4 crystal [23,24], Ba(NO 3 ) 2 crystal [25][26][27], and KGd(WO 4 ) 2 (KGW) crystal [28]. Specifically, Ba(NO 3 ) 2 crystal is a prevailing solid-state Raman gain media due to its high Raman gain coefficient of approximately 11 cm/GW at 1064 nm wavelength and narrow Raman line-width.…”
Section: Introductionmentioning
confidence: 99%